Technical Guide to Actions on Global Warming and Clean Development Mechanism in Sri Lanka - Batagoda, B.M.S.; Nissanka, S.P.; Wijekoon, Suren; Jaytilake, Avanthie (World Bank, Washington, DC, 2013)
The Ministry of Environment and Natural Resources of the Government of Sri Lanka is the apex body under which all environmental issues and policy matters are addressed. The Global Affairs Division of the Ministry of Environment and Natural Resources is tasked with formulating policy and strategic planning and liaise with the international organizations dealing with global environmental issues and is the Designated National Authority (DNA) for matters arising out of the Kyoto Protocol. Under the Kyoto protocol, the Clean Development Mechanism (CDM) provides for Green House Gas (GHG) mitigation projects that contribute towards sustainable development in developing nations and the net emission reductions can be traded to a developed nation to meet its Kyoto obligations. The report begins with green house effect with GHG emissions and their contributions to global warming. To highlight the gravity of the problem various projections are presented on future climate change, extreme weather events, sea level rise and their impact on developing countries. It describes the global initiative to tackle climate change and specifically details the Kyoto protocol.